A Psychological Map of Love. Alain de Botton’s Love Stories as Reflections of Sternberg’s Theory on Love - Ioana Unk ([sic])
This article aims to give a psychological interpretation to Alain de Botton’s novels On Love and The Course of Love, doubling the philosophical take on love that runs in the background of the novels. Robert Sternberg’s triangular theory of love will be applied to de Botton’s two novels, in an attempt to reach an understanding of love by means of psychological deconstruction, following the dynamic of the three components of the love triangle: passion, intimacy and decision \ commitment. References will also be made to Sternberg’s complementary theories on love, i.e. the theory that conceptualizes love as a story and the theory of love as a socio-cultural artefact.Key words: love, psychology, triangular theory, love story, cultureAlain de Botton’s book On Love, presented to the readers as a novel telling the love story of Chloe and the narrator, is a full-circle account that unfolds between two plane flights: on the first flight, from Paris to London, the two future lovers are seated one next to the other, and they meet and fall in love; the reverse flight, from Paris to London, takes the couple back home from a trip and ends with their break-up. The exact punctuation of the beginning and end of the romantic relationship is symptomatic of the whole structure of the book. The clearly delineated chapters and paragraphs correspond to as many moments in the couple’s relationship, thus allowing us to recreate with accuracy the milestones of their love story. The mere story-telling is doubled by the narrator’s voice that disassembles every event up to its inner detailed parts and deliversthe thoughts and rationale behind his actions. The reader is not left to guess, but discovers actively, together with the narrator, a keenly performed radiography of love.